Prediction of RF-EMF exposure levels in large outdoor areas through car-mounted measurements on the enveloping roads. (September 2016) - Aerts, Sam; Joseph, Wout; Maslanyj, Myron; Addison, Darren; Mee, Terry; Colussi, Loek; Kamer, Jos; Bolte, John
Abstract: Knowledge of spatial and temporal trends in the environmental exposure to radiofrequency electromagnetic fields (RF-EMF) is a key prerequisite for RF-EMF risk assessment studies attempting to establish a link between RF-EMF and potential effects on human health as well as on fauna and flora. In this paper, we determined the validity of RF exposure modelling based on inner-area kriging interpolation of measurements on the surrounding streets. The results vary depending on area size and shape and structural factors; a Spearman coefficient of 0.8 and a relative error of less than 3.5 dB are achieved on a data set featuring a closed measurement ring around a decently sized area (1 km 2, with an average minimum distance of the encircled area to the ring of less than 100 m), containing mainly low, detached buildings. In larger areas, additional inner-area sampling is advised, lowering the average minimum distance between sampled and interpolated locations to 100 m, to achieve the same level of accuracy. Highlights: RF-EMF exposure in area is modelled based on measurements on surrounding streets. Validation shows Spearman's ρ of 0.8 and errors below 2.5 dB in area of 1 km 2 . We advise a mean minimum distance between samples and interpolated area of 100 m.